Epidemiological profile of circulatory diseases - Pirondi, João Augusto Pinto (2023)
The poor lifestyle habits of the Brazilian population, combined with hereditary factors, have led to an increase in the incidence of circulatory diseases. It is worth noting that such pathologies affect different age groups of the population. As we already know, traditional therapies and primary prevention plans available aim to improve the patient's quality of life, preventing and treating their symptoms, but they have not proven to be very effective. The general objective of this study was to investigate the morbidity and mortality of cardiovascular diseases. The present study is associated with a bibliographical review, where the author appropriates previously presented and published knowledge, where the authors present an overview of a certain fact or proposed theme. The articles were published in the last five years. Data collection made it possible to gain knowledge about the regional and national panorama of the focal pathology, allowing the development of the study in search of achieving the general and specific objective and other proposals to collaborate in health promotion and disease prevention.